Convective overshoot and macroscopic diffusion in pure-hydrogen-atmosphere white dwarfs - Cunningham, Tim; Ludwig, Hans-Günter (Monthly notices of the Royal Astronomical Society, 2019)
We present a theoretical description of macroscopic diffusion caused by convective overshoot in pure-hydrogen DA white dwarfs using 3D, closed-bottom, radiation hydrodynamics CO5BOLD simulations. We rely on a new grid of deep 3D white dwarf models in the temperature range 11 400 ≤ Teff ≤ 18 000 K where tracer particles and a tracer density are used to derive macroscopic diffusion coefﬁcients driven by convective overshoot. These diffusion coefﬁcients are compared to microscopic diffusion coefﬁcients from 1D structures. We ﬁnd that the mass of the fully mixed region is likely to increase by up to 2.5 orders of magnitude while inferred accretion rates increase by a more moderate order of magnitude. We present evidence that an increase in settling time of up to 2 orders of magnitude is to be expected, which is of signiﬁcance for time-variability studies of polluted white dwarfs. Our grid also provides the most robust constraint on the onset of convective instabilities in DA white dwarfs to be in the effective temperature range from 18 000 to 18 250 K.